Efficacy of Aflibercept versus Ranibizumab in the treatment of diabetic macular edema - Xiu-Xian Wang (Press of International Journal of Ophthalmology (IJO PRESS), 2021)
AIM: To observe the efficacy of aflibercept and ranibizumab in the treatment of diabetic macular edema(DME).METHODS: Patients with DME who visited the ophthalmology department of Xingtai People's Hospital for the first time from November 2019 to February 2020 were included in the study. They were randomly divided into the aflibercept group and the ranibizumab group. 3+PRN(pro re nata)was used, and the interval time between two injections was at least 4wk. All patients were given three injections first. During follow-up, the patient's best corrected visual acuity(BCVA)and central foveal thickness(CFT)were used to determine whether to inject again. All patients were followed-up for 12mo. The changes of BCVA, CFT, intraocular pressure and injection times were recorded in two groups before and after treatment.RESULTS: During preoperative and postoperative follow-up, there were statistical differences in LogMAR BCVA and CFT of the two groups respectively(P<0.05). The comparison between the two groups showed no statistical significance during the BCVA and the CFT follow-up(P>0.05). At the end of follow-up, there was a statistical difference in the number of injections between the two groups(t= -6.403, P<0.05). The average number of injections was 6.094±0.689 in the aflibercept group and 7.231±0.652 in the ranibizumab group. No ocular complications or systemic adverse reactions occurred in all patients.CONCLUSION: Compared with intravitreal injection of ranibizumab and aflibercept for the treatment of DME can achieve similar treatment effect, but the number of injections is less in the aflibercept.